Zasądzenie odszkodowania z urzędu w procesie karnym - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article contains an assessment of ex-officio remedy in the Polish criminal trial. The author, after discussing the nature and presumptions concerning ex-officio remedy, shows doubts of interpretation arose in the background. She also makes an attempt to answer the question whether ex-officio remedy should be removed from the Code of Criminal Procedure, or remain in its present form.
Keywords: odsykodowanie z urzędu; odszkodowanie; prawo karne; przestępstwo